Curvularia lunata: identificação molecular e efeito antimicrobiano in vitro - SOARES, Nívia Rhennya do Nascimento (2022)
The fungus Curvularia sp. presents about 119 species and has morphological variability as its main characteristic. The species of this genus are classified as saprophytic organisms, endophytes and opportunistic pathogens, causing allergic sinusitis, pneumonia, endocarditis, mycetoma, onychomycosis, keratitis, brain abscesses, among others. Among the species of greatest interest, C. lunata is the main one isolated at sites of human and other living beings infections. In addition, the difficulty of identification is the main challenge, as there are limitations of conventional identification resources, making it necessary to use more sophisticated techniques. Another important approach is the use of secondary metabolites produced by fungi as an alternative source of antimicrobial activity. Thus, the aim of this study was to molecularly identify the Curvularia sp. and evaluate its extract on toxicity and antimicrobial profile. For this, the extraction of DNA from the fungus isolated from the environment was performed, using the polymerase chain reaction technique; extract production and toxicity tests in vitro using erythrocytes, in vivo in an alternative model using larvae of Tenebrio molitor, and for the antimicrobial profile it was tested the effect of the extract on three standard strains of Staphylococcus aureus, Escherichia coli and Candida albicans, evaluating the minimum inhibitory concentration, minimum bactericidal and fungicidal concentration, in addition to the anti-biofilm effect on abiotic surface. The results obtained confirmed, through molecular characterization, the environmental isolate belonging to the species C. lunata; The extract was non-toxic in in vitro toxicity assays using erythrocytes, in vivo in an alternative model using Tenebrio molitor larvae, broad antimicrobial activities were observed in the three microorganisms tested and significant reductions in biofilm biomass. Therefore, we conclude in this study that molecular techniques are important tools for species identification and that the extract produced from C. lunata secondary metabolites has promising potential for future therapeutic applications in bacterial and fungal infections.